Design of a microgripper for manipulation of micro-parts and biological cells - Nah, Siew Kuan (2008)
This thesis consists of 2 parts. This is part A. Precision control is a very important aspect in many areas of engineering. In the field of biotechnology, there is an increasing need for high precision sensing, positioning and manipulation of cells and other biological entities. In the field of medicine, positional accuracy greater than what human hands are capable of achieving is required in some surgeries. The introduction of a highly precision manipulator will assist in biological research on micro-sized cells, helping to save time and manpower costs. The use of micro robots for handling dangerous or unknown biological cells or drugs avoids human contact and the risk of contaminations.